External Arrhythmia Ablation Using Photon Beams: Ablation of the Atrioventricular Junction in an Intact Animal Model. (April 2017) - Lehmann, H. Immo; Deisher, Amanda J.; Takami, Mitsuru; Kruse, Jon J.; Song, Limin; Anderson, Sarah E.; Cusma, Jack T.; Parker, Kay D.; Johnson, Susan B.; Asirvatham, Samuel J.; Miller, Robert C.; Herman, Michael G.; et al.
Abstract : Background—: This study sought to investigate external photon beam radiation for catheter-free ablation of the atrioventricular junction in intact pigs. Methods and Results—: Ten pigs were randomized to either sham irradiation or irradiation of the atrioventricular junction (55, 50, 40, and 25 Gy). Animals underwent baseline electrophysiological evaluation, cardiac gated multi-row computed tomographic imaging for beam delivery planning, and intensity-modulated radiation therapy. Doses to the coronary arteries were optimized. Invasive follow-up was conducted ⩽4 months after the irradiation. A mean volume of 2.5±0.5 mL was irradiated with target dose. The mean follow-up length after irradiation was 124.8±30.8 days. Out of 7 irradiated animals, complete atrioventricular block was achieved in 6 animals of all 4 dose groups (86%). Using the same targeting margins, ablation lesion size notably increased with the delivered dose because of volumetric effects of isodose lines around the target volume. The mean macroscopically calculated atrial lesion volume for all 4 dose groups was 3.8±1.1 mL, lesions extended anteriorly into the interventricular septum. No short-term side effects were observed. No damage was observed in the tissues of the esophagus, phrenic nerves, or trachea. However, histology revealed in-field beam effects outside of the target volume. Conclusions—: Single-fraction doses as low as 25 Gy caused a lesion with interruption of cardiac impulse propagation using this respective target volume. With doses of ⩽55 Gy, maximal point-doses to coronary arteries could be kept <7Gy, but target conformity of lesions was not fully achieved using this approach.